Does transbronchial lung cryobiopsy give useful information in asthmatic patients? - Colella, Sara; Ravaglia, Claudia; Massaccesi, Chiara; D’Emilio, Vittorio; Panella, Gianluca; Fioretti, Federica; Conte, Emanuele Giovanni; Collina, Guido; Pela, Riccardo; Poletti, Venerino (Multidisciplinary Respiratory Medicine, 2019)
Introduction: Lung biopsy in asthmatic patients is justified in case of atypical presentations of asthma, when other differential diagnoses, such as hypersensitivity pneumonitis or eosinophilic granulomatosis with polyangiitis, could be possible or for research purposes. Aim: We aim to describe the utility and the safety of TBLC (transbronchial lung cryobiopsy) in asthmatic patients, providing data on the pathological changes occurring in the airways and in the lung parenchyma. Methods: We reviewed asthmatic patients that underwent TBLC, that eventually had only a final diagnosis of asthma. Results: Three patients were detected. TBLC described pathological abnormalities in peribronchiolar and alveolar spaces already well identified with SLB (surgical lung biopsy); the pathological information provided could be useful to better understand the pathobiology of the disease. Finally, we had no complications, confirming a satisfactory safety profile of TBLC. Conclusion: We suggest the potential role of TBLC in asthmatic patients: its safety and its acceptable diagnostic accuracy lead to consider this procedure instead of SLB when histological changes in lung parenchyma are needed for the differential diagnosis. Furthermore, TLBC could be useful for research in the pathobiology of asthma and severe asthma.